Conventional Antimicrobial and Medicinal Plants from a Traditional Medicine Market in South Africa: An Interactive Antimicrobial and Toxicity Study - Zelna Booth; Sabiha Essack; Sandy van Vuuren (Antibiotics)
Background: The World Health Organization (WHO) has proposed the use of integrative medicine to achieve extended healthcare coverage in developing countries facing high morbidity. Traditional remedies are frequently employed to prevent and treat infections among South Africans; however, the ways in which they interact with conventional antimicrobials are largely unknown. Therefore, this study aimed to explore the interactions between commonly traded medicinal plants at a traditional medicine market in KwaZulu-Natal (KZN), South Africa, and conventional antibiotics and antifungals. Methods: To determine the interactive antimicrobial profiles for plant/conventional antimicrobial combinations, minimum inhibitory concentration (MIC) assays were performed against ESKAPE pathogens and the yeasts Candida albicans and Candida glabrata. Calculated fractional inhibitory concentration (ΣFIC) values were used to identify synergism or antagonism, with synergistic interactions further tested in vitro for toxicity. Results: A total of 952 combinations were tested, of which 5.8% and 54.6% of the plant/antibiotic combinations were synergistic and antagonistic, respectively; additionally, 1.7% and 58.6% of the plant/antifungal combinations showed synergism or antagonism, respectively. The most toxic plant/antibiotic combination was Artemisia afra with doxycycline (71.1% mortality). The most toxic plant/antifungal combination was Acorus calamus with fluconazole (78.8% mortality). Conclusions: When medicinal plants acquired from a traditional medicine market in South Africa are used in combination with conventional antibiotics and antifungals, more than half of the combinations exhibit antagonism, which is concerning.